Effect and in silico characterization of genetic variants associated with severe spermatogenic disorders in a large Iberian cohort - Cerván‐Martín, Miriam (2022)
IVIRMA Group, Lisbon Clinical Group: Alberto Pacheco, Cristina González, Susana Gómez, David Amorós, Jesus Aguilar, Fernando Quintana, Carlos Calhaz-Jorge, Ana Aguiar, Joaquim Nunes, Sandra Sousa, Maria Graça Pinto, Sónia Correia